1989
DOI: 10.1093/oxfordjournals.jbchem.a122758
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Contractile Properties of Rabbit Skeletal Muscle by Ethylene Glycol1

Abstract: The effect of ethylene glycol on the contractile properties of skeletal muscles was studied using glycerinated rabbit psoas muscle fibers. Measurements were made at an ionic strength of 0.2 M, pH 7.0, and at 10 degrees C. Ethylene glycol reversibly reduced isometric tension, active stiffness, the tension-to-stiffness ratio, and the shortening velocity at zero load (Vo) in a dose-dependent fashion. Ethylene glycol also reduced the Ca sensitivity for contraction. The extent of the reduction in Vo by ethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…In contrast with the results with DMSO ( Figure 7A), S1 MgATPase was unaltered by ethylene glycol ( Figure 7B). The data shown for acto-S1 ( Figure 7B) are consistent with earlier studies in which acto-S1 (ATPase) and fibres (contraction velocity) were used [16,27]. 1 µM), and the reaction was started with 5 mM ATP.…”
Section: Affinity For Actinsupporting
confidence: 88%
See 4 more Smart Citations
“…In contrast with the results with DMSO ( Figure 7A), S1 MgATPase was unaltered by ethylene glycol ( Figure 7B). The data shown for acto-S1 ( Figure 7B) are consistent with earlier studies in which acto-S1 (ATPase) and fibres (contraction velocity) were used [16,27]. 1 µM), and the reaction was started with 5 mM ATP.…”
Section: Affinity For Actinsupporting
confidence: 88%
“…However, a low con-centration of DMSO (1 %, v\v) depressed contraction in isolated skinned fibres of the frog, suggesting a direct effect on the contractile apparatus [35]. In preliminary experiments we found that DMSO, like ethylene glycol [27], also inhibits isometric tension in mammalian skinned fibres, but it can either activate or inhibit the hydrolysis of ATP by myosin in solution, depending on the cation present [36]. Here we have examined the effects of DMSO on the steady-state properties of myosin subfragment 1 (S1), acto-S1, myofibrils and skinned fibres, and in motility assays using acto-heavy meromyosin (HMM).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations